سبل تبني التسويق السياحي لتدعيم التنمية السياحية - حسام الدين, جوادي; حمزة, خزان; توفيق, داودي (University of eloued جامعة الوادي, 2022)
"تعد السياحة أحد القطاعات الأكثر أهمية وديناميكية عبر العالم، فهي وسيلة فعالة لجلب مداخيل هامة من العملة الصعبة وامتصاص البطالة، وكذا المساهمة في الدخل الوطني، وزيادة الإيرادات للدولة، فقد أصبحت تعتبر حاليا صناعة تصديرية لها دور فعال في تحقيق التنمية اقتصاديا واجتماعيا، ولا يتحقق هذا إلا بالاهتمام الكبير للتسويق السياحي الذي يعتبر محرك للسياحية على المستوى الوطني والعالمي، فهو يعتبر أداة فعالة لتسيير المؤسسات السياحية وجعلها مرنة تستجيب مع اضطرابات السوق. وهذا ما أكدته النتائج المتوصل إليها حيث نجد أن القطاع السياحي في كل من دولتي تونس والمغرب ان غياب مخطط للتنمية السياحية يعكس القدرات السياحية الموجودة في البلد، ويتبنى فعليا تطبيق قواعد وأسس التسويق السياحي، وبالتالي فان تطوير السياحة لا يعتمد فقط على توفر الموارد السياحية ومناطق الجذب السياحي وإنما في كيفية استخدام واستغلال تلك الموارد في عملية تنمية السياحة.""Tourism is one of the most important and dynamic sectors across the world. It is an effective way to bring in important incomes from hard currency and absorb unemployment, as well as contribute to national income and increase revenues for the state. It is now considered an export industry with an effective role in achieving economic and social development. This is not achieved Except for the great interest in tourism marketing, which is considered the engine of tourism at the national and global levels; it is considered an effective tool for managing tourism institutions and making them flexible. For pocket with wet first. This was confirmed by the results obtained, as we find that the tourism sector in both Tunisia and Morocco states that the absence of a tourism development plan has some of the existing tourism capabilities in the country, and it is intended to apply the rules and tourism marketing, and therefore the development of tourism does not only know about the resources of the arena and the delay of love At the College of Dr. Wacht Le Laure In the basket of the night of tourism"
ماستر تسويق
Keywords: السياحة، التسويق السياحي، التنمية السياحة، تونس،المغرب.; tourism, tourism marketing, tourism developpement,tunisia,Morocco